2022
DOI: 10.1001/jamanetworkopen.2021.48871
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Placement of a Supraglottic Airway Device vs Endotracheal Intubation on Return of Spontaneous Circulation in Adults With Out-of-Hospital Cardiac Arrest in Taipei, Taiwan

Abstract: IMPORTANCEPrehospital advanced airway management with either initial endotracheal intubation (ETI) or initial supraglottic airway (SGA) insertion in patients with out-of-hospital cardiac arrest (OHCA) remains controversial. OBJECTIVE To compare the effectiveness of ETI and SGA in patients with nontraumatic OHCA. DESIGN, SETTING, AND PARTICIPANTS The Supraglottic Airway Device vs Endotracheal intubation (SAVE) trial was a multicenter cluster randomized clinical trial conducted in Taipei City, Taiwan. Individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Hence, alternative methods for advanced airway management may find a place in patient management. However, a recent trial found that supraglottic placement of a supraglottic airway device was not superior to endotracheal intubation after cardiac arrest [ 30 ]. Fluid administration is usually required concurrently, as the introduction of positive intrathoracic pressure can induce a severe hypotension in hypovolaemic patients.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, alternative methods for advanced airway management may find a place in patient management. However, a recent trial found that supraglottic placement of a supraglottic airway device was not superior to endotracheal intubation after cardiac arrest [ 30 ]. Fluid administration is usually required concurrently, as the introduction of positive intrathoracic pressure can induce a severe hypotension in hypovolaemic patients.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, when an advanced airway is used, SGA is suggested in settings with a low ETI success rate, leaving the use of endotracheal tubes to professional rescuers with high ETI success rates, i.e., >95% within two attempts [ 14 ]. The “Supraglottic Airway Device vs. Endotracheal Intubation” (SAVE) trial [ 17 ] compared the effectiveness of ETI vs. SGA in adult patients with non-traumatic OHCA, targeting sustained ROSC as the primary outcome. EMS systems were cluster-randomized to ETI or SGA, and a total of 936 patients (517 in the ETI group and 419 in the SGA group) were included in the primary analysis.…”
Section: Results and Discussion Of 2022 Rctsmentioning
confidence: 99%
“…Sustained ROSC was achieved in 26.9% of patients after ETI vs. 25.8% after SGA. No differences in survival to hospital discharge and neurological recovery were observed [ 17 ]. Thus, the SAVE trial, by confirming the equivalency of these two airway strategies in terms of ROSC and long-term outcome, consistently with the earlier AIRWAYS 2 trial [ 18 ], supports current clinical recommendations [ 14 ].…”
Section: Results and Discussion Of 2022 Rctsmentioning
confidence: 99%
“…Network meta-analysis of randomized control trials reveal that ET tube placement and supraglottic airway (SGA) do increase the rate of ROSC compared to BVM [ 44 ]; the success rate of intubation greatly influenced the results. In one randomized clinical trial from Taipei EMS, among patients with OHCA, the initial airway management with ETI by ALS was associated with a higher probability of prehospital ROSC compared with SGA, especially among the subgroups of non-shockable rhythm, nonpublic collapse, arrested witnessed, call to airway time less than 14 minutes, and age 77 years or older, indicating that the shorter ALS response time may be related to a better chance of prehospital ROSC [ 45 ]. Chiang et al [ 23 ] also found that successful out-of-hospital intubation with OHCA patients increased the odds of sustained ROSC, survival to hospital discharge, and favorable neurological outcome compared to BVM.…”
Section: Discussionmentioning
confidence: 99%